The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0239806
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutation status concordance between the primary tumor and the corresponding metastasis in patients with rectal cancer

Abstract: Introduction Oncogenic mutation within the KRAS gene represents a negative predictor for treatment response to anti-epidermal growth factor receptor (EGFR) in patients with colorectal cancer. Recently, we have shown no relevant heterogeneity for KRAS mutation status within and between pre-and posttherapeutic samples from the primary tumor in patients with locally advanced rectal cancer. The aim of this study was to evaluate the intertumoral heterogeneity of KRAS mutation status between the primary tumor and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
6
1
1
Order By: Relevance
“…However, few studies have investigated the role of KRAS mutations in patients with LARC. Our results showed that KRAS mutations were present in 24.7% of patients, a lower frequency than reported in other publications [ 20 , 21 , 22 ]. In our study, we found that KRAS mutations were significantly associated with poorer OS and PFS in LARC patients receiving nCRT, but there was no relation between KRAS mutations and TRG.…”
Section: Discussioncontrasting
confidence: 80%
“…However, few studies have investigated the role of KRAS mutations in patients with LARC. Our results showed that KRAS mutations were present in 24.7% of patients, a lower frequency than reported in other publications [ 20 , 21 , 22 ]. In our study, we found that KRAS mutations were significantly associated with poorer OS and PFS in LARC patients receiving nCRT, but there was no relation between KRAS mutations and TRG.…”
Section: Discussioncontrasting
confidence: 80%
“…Subgroup analyses stratified by ethnicity showed that in Asian populations, KRAS, BRAF, and TP53 mutations, including lymph node and distant metastasis, were associated with mCRC, whereas only TP53 mutations promoted mCRC in Caucasians. Jo et al [ 11 ] investigated the difference between mCRC primary tumors and mCRC metastatic tissues and identified a significant concordance of KRAS mutation status in 81.18% (9/11) of patients ( P = 0.03271). Only two patients showed intertumor heterogeneity.…”
Section: Genomic Variation Of Mcrcmentioning
confidence: 99%
“…RAS gene expression was consistent between CRC and metastatic lesion. Probably, occurrence of metachronous liver metastasis may be predicted by postoperative genetic mutations [ 114 ]. Nevertheless, specific location and pattern of tumor metastasis related to KRAS are always disputed.…”
Section: Tissue-based Biomarkersmentioning
confidence: 99%